The Artist as an Exemplary Consumer - Groys, Boris (Filozofski vestnik, 2016)
In our time the artist has disappeared as an unique individual creator but at the same time he has re-emerged as the subject of the aristocratic gaze, as the exemplary consumer. The artists, as a media-artist, has also gained much greater control over the gaze of the spectator. Accordingly, the art system of today has by no means collapsed. Rather, it has become stronger and better organized, so that it can function as the place where such an aristocratic gaze can manifest itself.